Theories, objectives and principles of corporate insolvency law: A comparative study between Malaysia and UK - Azmi, Ruzita (2013)
The corporate insolvency affects many parties that have interests in the continued existence of the company or business and those interests may conflict and cause tensions between them. The existence of corporate insolvency law is associated with an attempt to balance the interests of those who are ‘stakeholders’ in corporate insolvency, such as creditors, employees, local community and the public. Whether the role of insolvency law is to focus on the creditors’ interest or whether insolvency law has more roles to play and wider range of interests to be considered under insolvency laws has pointed to the debates on the underlying principles such as the objectives and theoretical foundations of corporate insolvency law. In view of the importance of theories underpinning corporate insolvency law to a proper understanding of the objectives and principles of the law, it is necessary to review various theories of corporate insolvency. These theories are mostly constructed by scholars in the US and UK in their pursuit of finding the objective of corporate insolvency law. In order to uncover the real objectives or purpose and principles of corporate insolvency law by reviewing corporate insolvency law theories, the authors collected information through secondary data analysis. Sources of the data are textbooks, articles from law journal and law review also report of corporate insolvency. Considering that Malaysian law has been significantly influenced by the English common law, the theories and objectives as well as principles of corporate insolvency law in Malaysia is compared to theories and objectives in the UK. It is recognized that the difference in the underlying theories and objectives produced different types of insolvency principles and rules. This paper will examine the theories of corporate insolvency laws. This paper will also analyse and compare the objectives and principles of corporate insolvency law in Malaysia and UK.